Anti-tumor and immunomodulatory activity of the aqueous extract of Sarcodon imbricatus in vitro and in vivo. Issue 1 (11th December 2019) - Tan, Xupeng; Chen, Wang; Jiao, Chunwei; Liang, Huijia; Yun, Hao; He, Chunyan; Chen, Jiaming; Ma, Xiaowei; Xie, Yizhen
Abstract : Sarcodon imbricatus ( S. imbricatus ), a well-known edible mushroom, is one of the most commonly consumed wild mushrooms in China because of its nutritional value. Abstract : Sarcodon imbricatus ( S. imbricatus ), a well-known edible mushroom, is one of the most commonly consumed wild mushrooms in China because of its nutritional value. Previous studies have demonstrated that S. imbricatus has immunoregulatory activity. We previously described the potential anti-tumor activity of several types of mushrooms, including S. imbricatus. In this study, the results demonstrate that an aqueous extract of S. imbricatus (SIE) effectively inhibits the growth, migration, and invasion properties of breast cancer cells in vitro and reduces tumor growth in vivo . In addition, the SIE increased serum concentrations of interleukin (IL)-2, IL-6 and tumor necrosis factor-α, natural killer cell activity and the viability of splenocytes and reduced the expression of programmed cell death-Ligand 1 (PD-L1) in 4T1 tumor-bearing mice. Collectively, these results are the first demonstration that the SIE has anti-tumor and immunomodulatory effects in the 4T1 mouse breast cancer model. These findings provide a scientific rationale for the potential therapeutic use of S. imbricatus in breast cancer patients.